2010
DOI: 10.3892/or_00001003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immune response according to the metastatic status in the regional lymph nodes in patients with gastric carcinoma

Abstract: Abstract. The immunological response in the regional lymph nodes (LN) of gastric cancer patients who had metastasis was studied by investigating both the degree of metastasis and the maturation status of dendritic cells (DCs). A total of 732 LNs was obtained from 29 gastric cancer patients, including 25 patients whose LNs were pathological metastasis-negative and 4 patients with metastasis-positive LNs. Micrometastasis (MM) in the LNs was analyzed by immunohistochemical staining of cytokeratin (CK) (IHC-MM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The majority of the studies (n = 18) did not evaluate the association between LN OTC presence and survival, or were inconclusive in this respect [3,5,6,10,11,23,25,26,27,28,31,36,38,40,45,46,47] (table 3). Several articles (n = 16) reported that OTC were associated with worse prognosis [1,2,7,12,13,14,16,17,19,22,29,33,35,39,41,43] (table 4), while in some (n = 8) such an association was not found [4,15,18,20,21,32,34,44] (table 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the studies (n = 18) did not evaluate the association between LN OTC presence and survival, or were inconclusive in this respect [3,5,6,10,11,23,25,26,27,28,31,36,38,40,45,46,47] (table 3). Several articles (n = 16) reported that OTC were associated with worse prognosis [1,2,7,12,13,14,16,17,19,22,29,33,35,39,41,43] (table 4), while in some (n = 8) such an association was not found [4,15,18,20,21,32,34,44] (table 5).…”
Section: Resultsmentioning
confidence: 99%
“…With PCR/RT-PCR methods, the variability of markers was greater than with IHC, the carcinoembryonic antigen (CEA) being the most frequently used (n = 7) [5,10,27,31,34,44,47]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Despite the presence of CD8 C T cells in the primary tumor, a lower percentage of effector CD8 C T cells has also been found in the metastatic or pre-metastatic LN of CRC patients, suggesting that cell-mediated immunity also depends on the localization and functional role of CD8 C T cells in the tumor-draining LN. 18,19 Thus, defining the potential CD8 C T cell subsets in LNs is essential to understanding their roles and mechanisms in tumor immunopathogenesis. CD169, also known as sialoadhesin or sialic acid binding immunoglobulin-like lectin, is the founding member of the Siglec superfamily.…”
Section: Introductionmentioning
confidence: 99%